The Shame and Guilt Scales of the Test of Self-Conscious Affect-Adolescent (TOSCA-A): Psychometric Properties for Responses from Children, and Measurement Invariance Across Children and Adolescents - Watson, Shaun D.; Gomez, Rapson; Gullone, Eleonora (Frontiers in Psychology, 2016)
This study examined various psychometric properties of the items comprising the shame and guilt scales of the Test of Self-Conscious Affect-Adolescent (TOSCA-A) in a group children between 8 and 11 years of age. A total of 699 children (367 females and 332 males) completed these scales, and also measures of depression and empathy. Confirmatory factor analysis (CFA) provided support for an oblique two-factor model, with the originally proposed shame and guilt items comprising shame and guilt factors, respectively. There was good internal consistency reliability for the shame and guilt scales, with omega coefficient values of .77 and .81 for shame and guilt, respectively. Also, shame correlated with depression symptoms positively (.34, p < .001) and had no relation with empathy (-.07, ns). Guilt correlated with depression symptoms negatively (-.28, p < .001), and with empathy positively (.13. p < .05). Thus there was support for the convergent and discriminant validity of the shame and guilt factors. Multiple-group CFA comparing this group of children with a separate group of adolescents (320 females and 242 males), based on the chi-square difference test, supported full metric invariance, the intercept invariance of 17 of the 30 shame and guilt items, and higher latent mean scores among children for both shame and guilt. The non-equivalency for intercepts and mean scores were of small effect sizes. Comparisons based on the difference in root mean squared error of approximation values supported full measurement invariance and no group difference for latent mean scores. The findings in the current study support the use of the TOSCA-A in children and the valid comparison of scores between children and adolescents, thereby opening up the possibility of evaluating change in the TOSCA-A shame and guilt factors over these developmental age groups.